A case study of VLF phase and amplitude variation at 12.1 kHz (Aldra) in Iceland - Araki, Takashi; Sato, Natsuo; Fujii, Ryoichi; Kikuchi, Takashi; Kokubun, Susumu (1986)
P(論文) The phase and the field strength of 12.1-kHz VLF signals propagating from Aldra, Norway have been continuously recorded at Tjornes, Iceland using a phase-locked receiver with a loop antenna parallel to the great circle path between Norway and Iceland. Nighttime records represent irregular phase and amplitude fluctuations and sometimes involve quasi-sinusoidal fluctuations. The phase and amplitude change associated with cosmic noise absorption (CNA) are observed on the VLF signals, for which the phase is advanced with the change of the electron number density distribution of lower ionosphere. departmental bulletin paper